Genetic variants in RET, ARHGEF3 and CTNNAL1, and relevant interaction networks, contribute to the risk of Hirschsprung disease - Wang, Yang (Aging (Albany NY), 2020)
Hirschsprung disease (HSCR), the most common enteric neuropathy, stands as a model for complex genetic disorders. It has recently been demonstrated that both ARHGEF3 and CTNNAL1 map to the RET-dependent HSCR susceptibility loci. We therefore sought to explore whether genetic variants within RET, ARHGEF3 and CTNNAL1, and their genetic interaction networks are associated with HSCR. Taking advantage of a strategy that combined the MassArray system and gene-gene interaction analysis with case-control study, we interrogated 38 polymorphisms within RET, ARHGEF3 and CTNNAL1 in 1015 subjects (502 HSCR cases and 513 controls) of Han Chinese origin. There were statistically significant associations between 20 genetic variants in these three genes and HSCR. Haplotype analysis also revealed some significant global P values, i.e. RET_ rs2435357-rs752978-rs74400468-rs2435353-rs2075913-rs17028-rs2435355 (P = 3.79×10(-58)). Using the MDR and GeneMANIA platforms, we found strong genetic interactions among RET, ARHGEF3, and CTNNAL1 and our previously studied GAL, GAP43, NRSN1, PTCH1, GABRG2 and RELN genes. These results offer the first indication that genetic markers of RET, ARHGEF3 and CTNNAL1 and relevant genetic interaction networks confer the altered risk to HSCR in the Han Chinese population.